Lymphoma‐associated acquired von Willebrand syndrome responsive to splenectomy: A case report. Issue 3 (31st May 2022) - Khadadah, Fatima; Rupani, Natasha; Scott, Jordan; Trinkaus, Martina; Teitel, Jerome; Sholzberg, Michelle
Abstract: A previously healthy 33‐year‐old female presented with a large hematoma over her right knee after kneeling. She was found to have pancytopenia and massive splenomegaly. Von Willebrand Factor (VWF) antigen level was 0.38 units/ml, ristocetin cofactor activity 0.13 units/ml, and VWF multimeric distribution was normal. Bone marrow examination revealed an indolent B‐cell lymphoma. Diagnosis was consistent with acquired von Willebrand syndrome as an autoimmune epiphenomenon of a lymphoma. Diagnostic and therapeutic splenectomy under hemostatic coverage was performed. VWF antigen levels and activities immediately normalized postoperatively and remained within the normal range several months later. Splenic pathology confirmed hairy cell leukemia with a BRAF mutation.